Twilite Orchestra: An Indonesian Pops Orchestra - Rachmawanti, Ranti (TAWARIKH, 2015)
ABSTRACT: Music is one of the culture elements which change and improve fast in the context of popular culture. Influenced by this culture, there are many musical innovations in Indonesia. Many music communities are made up of various formats, style, and genre, either tradition or Western. One of the Western music format and music communities developed in this country is orchestra, a group of musicians playing instrument in harmony. In the beginning, however, orchestra was developed in Europe on the 17th century. Along with the changes and the passing time, the music played by the orchestra had started to change. And orchestra may be not a new thing to Indonesia. There are evidences which show that orchestra has long been well-known. Indonesian orchestra is growing rapidly by the presence of the Twilite Orchestra as an Indonesian Pops Orchestra. This article explains the research result of Twilite Orchestra as one of Indonesian Pops orchestra. Main idea of this research is to uncover and describes the Twilite Orchestra characteristics, functions, and roles of Twilite Orchestra within the popular culture in Indonesia. This research used qualitative method with ethnographical approaches to identify all facts discovered during research. The conclusions of this research show that Twilite Orchestra moves in two ways, which are the idealism of a vision to create a real Indonesian orchestra and to be a part of music industry. At the end, these two ways are connected to each other in their making. Music industry becomes a supporting factor which creates the idealism of Twilite Orchestra to be an Indonesian Pops Orchestra.KEY WORDS: Music, Twilite orchestra, popular culture, music industry, idealism of a vision, and characteristics, functions and roles of Twilite Orchestra.Â About the Author: Ranti Rachmawanti is a Doctoral Student at the Cultural Studies Program, Faculty of Humanities UNPAD (Padjadjaran University), Jalan Raya Bandung-Sumedang Km.15, Jatinangor, Sumedang, West Java, Indonesia. The author can be contacted via her e-mails at: ranti13005@student.unpad.ac.id and ranti02@gmail.comHow to cite this article? Rachmawanti, Ranti. (2015). âTwilite Orchestra: An Indonesian Pops Orchestraâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.169-176. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (November 24, 2014); Revised (February 2, 2015); and Published (April 28, 2015).